Organizational Culture And Work Environment On Employee Performance At The Kunir Community Health Center - Khairullah, Mohammad Noor (Jurnal Ilmu Manajemen Advantage, 2023)
Human resource management is a way of managing human resources in an organization in order to achieve the goals of the organization optimally through developing human resources themselves. This research aims to analyze and determine the influence of the work environment and organizational culture on employee performance at the Kunir Health Center, Lumajang Regency. The type of research used in this research is quantitative research. The population used in this research were employees of the Kunir Health Center, Lumajang Regency. The sampling technique used in this research was the saturated sampling method, which is a sampling technique that takes all members of the population in the object as samples. Data collection was carried out by distributing questionnaires with a sample size of 45 respondents. The analytical method used in this research is multiple linear regression analysis. The research results show that the work environment and organizational culture have a positive and significant effect on employee performance at the Kunir Community Health Center, Lumajang Regency.